Credit Risk Management in Major British Banks - Zhao, Xiuzhu (2007)
Abstract Credit risk is always treated as the major risk inherent in a bank's banking and trading activities. And if not well managed, this kind of risk may drag a bank into great trouble or even bankruptcy, which can be proved by various bank failure cases. For banks, managing credit risk is not a simple task since comprehensive considerations and practices are needed for identifying, measuring, controlling and minimizing credit risk. In this dissertation, the credit risk management practices of major British banks are examined through the quantitative research on all Major British Banking Group members and qualitative analysis on the four sample banks. The key areas in the generalization and comparison of techniques and practices of sample banks are chosen according to the Basel (1999, 2000) requirements, which are also adopted as benchmarks in the evaluation of banks credit risk management. The robustness and weakness of larger and smaller major British banks in managing credit risk are identified respectively, which indicates the areas for further improvements as well.